KORUPSI DALAM RANAH KEHUTANAN - Helmi Helmi (Jurnal Yudisial, 2010)
ABSTRACTThis verdict analysis research on a delict in the field of forestry violence as regulated in Act Number 41 of 1999. The verdict certified that the accused was guilty to commit a delict as stipulated in primary indictment. The findings of this research from the verdict are the verdict did not apply the provisions of the procedural law. The verdict also was correct in determining the material legal ground to prove and declare the accused guilty, but it did not prove the element of “by intention” as a form of guilt as pointed. Instead, this verdict applied syllogism reasoning in which the judges have conducted a construction based on the rule of law, and the verdict deployed the value of justice in its legal ground since the verdict was based on legal fact and also in its punishment. The verdict also accommodated the value of utility with the aim of speciale preventie (special prevention), generale preventie (general prevention) and the philosophy of retributive punishment.Keywords: crime on forestry, instruments of evidence, philosophy of punishment.ABSTRAKPenelitian putusan hakim ini dalam perkara tindak pidana bidang kehutanan sebagaimana diatur dalam UU Nomor 41 Tahun 1999. Putusan telah menyatakan bahwa terdakwa bersalah melakukan kesalahan sebagaimana dituduhkan dalam dakwaan premair. Dalam penelitian ini ditemukan beberapa hal seperti putusan tidak memenuhi beberapa syarat sebagaimana yang ditentukan dalam hukum acara. Penulis menilai bahwa putusan ini sudah tepat menentukan dasar hukum materiil untuk membuktikan kesalahan, akan tetapi majelis hakim salah dalammenyebutkan unsur delik dalam analisis pembuktian unsur delik dengan tidak mencantumkan unsur dengan sengaja sehingga tidak dibuktikan di persidangan. Selain itu, putusan hakim ini sudah melakukan penalaran hukum yang logis berdasarkan fakta hukum dan hukuman, mengakomodir nilai keadilan baik dasar dalam dasar hukumnya maupun dari segi pidananya yang memuat nilai kemanfaatan dari perspektif specile preventie dan generale preventie, sertamenerapkan falsafat pemidanaan yang retributif.Kata kunci: kejahatan bidang kehutanan, instrumen pembuktian, falsafah pemidanaan.